Immunogenicity and safety of an investigational AS02v-adjuvanted hepatitis B vaccine in patients with renal insufficiency who failed to respond or to maintain antibody levels after prior vaccination: results of two open, randomized, comparative trials - Tielemans, Christian L.; Vlasak, Jiri; Kosa, Dezider; Billiouw, Jean-Marie; Verpooten, Gert A.; Mezei, Ilona; Ryba, Miroslav; Peeters, Patrick C.; Mat, Olivier; Jadoul, Michel Y.; Polakovic, Vladimir; Dhaene, Michel; et al. (Vaccine, 2011)
An investigational AS02v-adjuvanted hepatitis B (HB-AS02) was compared with a licensed conventional recombinant hepatitis B vaccine (HBVAXPRO™; Sanofi Pasteur MSD, Lyon, France) in pre-dialysis, peritoneal dialysis and hemodialysis patients aged ≥18 years who had failed either to respond to prior vaccination with a conventional hepatitis B vaccine (Study A; n=251) or to maintain protective antibody concentrations after prior hepatitis B vaccination (Study B; n=181). These were open, randomized, comparative trials. Mean (range) age was 65.9 (31-92) and 64.6 (29-92) years in the two studies, respectively. In Study A, two doses of HB-AS02 given one month apart were found to be superior to two doses of the licensed vaccine in terms of seroprotection rate (76.9% versus 37.6%) and anti-HBs geometric mean antibody concentration (GMC; 139.3 versus 6.9mIU/ml), with antibody concentrations ≥100mIU/ml in 61.1% and 15.4% of subjects in the two groups, respectively. In Study B, one month after administration of a single booster dose, seroprotection rates were 89.0% in the HB-AS02 group and 90.8% in the licensed vaccine group, 81.3% and 60.9% of subjects had antibody concentrations ≥100mIU/ml, and anti-HBs GMCs were 1726.8 and 189.5mIU/ml. HB-AS02 was found to be more reactogenic than the licensed vaccine. In summary, the investigational HB-AS02 vaccine induced higher seroprotection rates and anti-HBs GMCs than a licensed conventional hepatitis B vaccine in uremic patients who had failed to respond or to maintain protective antibody titers after prior hepatitis B vaccination.
Gesehen am 03.11.2022
Erstmals online zugänglich am 16. Dezember 2010
Im Titel ist der Buchstabe v nach "AS02" tiefgestellt